Historical dictionary of Malaysia - Ooi, Keat Gin, 1959- (Lanham, MD ; Plymouth, UK : Scarecrow Press, 2009)
"Historical Dictionary of Malaysia encapsulates the development of the country from prehistory to the early years of the 21st century. It covers not only Malaysia's history but also its politics, economy, multi-ethnic society, multiculturalism, scientific and technological developments, and the state of its environment. A host of contemporary issues and challenges are featured, including ethnic polarization, economic equity, and polygamy; concepts like Ketuanan Melayu (Malay Dominance), Malaysian Malaysia, Malay, and Islam Hadhari (Civilizational Islam); and terms, such as Ali Baba business, kiasi, bejalai, and Twenty Points. More than 500 cross-referenced dictionary entries cover everything from ethnohistorical subjects to culinary favorites and national personalities. A chronology, an introductory essay, appendixes, and a bibliography complement the dictionary entries, enhancing this authoritative and up-to-date guide."--BOOK JACKET.
Includes bibliographical references (p. 343-417).
Keywords: Malaysia -- History -- Dictionaries